The Multicultural Education and National Unity in Malaysia’s Diverse Society - Masruatus Saadah (CV Edujavare Publishing, 2024)
The multicultural character of Malaysian society has long been recognized as one of the nation's greatest strengths as well as one of its most significant challenges. Comprising diverse ethnic groups, including Malays, Chinese, Indians, and various indigenous communities, Malaysia requires educational strategies that promote social cohesion, mutual respect, and national integration. Multicultural education has emerged as a crucial approach for fostering understanding among different cultural groups while strengthening a shared sense of national identity. This study examines the role of multicultural education in promoting national unity within Malaysia’s diverse society through a comprehensive review of relevant literature and educational policies. The findings indicate that multicultural education contributes significantly to intercultural understanding, tolerance, social inclusion, and civic responsibility among students. Furthermore, educational initiatives that emphasize cultural diversity, shared national values, and intercultural dialogue help reduce prejudice and strengthen social harmony. The study concludes that multicultural education serves as a strategic instrument for sustaining national unity and preparing future generations to participate constructively in an increasingly diverse and globalized society.